EKSPLORASI ETNOMATEMATIKA NGADHU DAN BHAGA DALAM KAITANNYA DENGAN PEMBELAJARAN MATEMATIKA PADA MASYARAKAT DESA UBEDOLUMOLO KABUPATEN NGADA - Eugenius Djara; Natalia Peni; Maria Trisna Sero Wondo (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
This study aims to determine: (1) to identify the structure of ngadhu and bhaga in Ubedoulumolo Village of Ngada District. (2) Explain the relation of ngadhu and bhaga to mathematics learning in school. The research method used is qualitative with an ethnographic approach. The subjects of this study consisted of three informants (pengu chief, and traditional elders of pengu and gelo tribe). Using observation and interview techniques, supported by documentation, and using qualitative descriptive analysis. The results of the study showed ngadhu and bhaga has related to mathematics, that is the geometry concept. The geometry concept found in ngadhu is: (1) pole ngadhu (made of sebu tree) in the form of a tube; (2) base of ngadhu is composed of a stone in a circle; (3) the roof of ngadhu (material of reeds and palm fibre) in the shape of a cone; (4) bhenga (2 roof support posts) in the form of a beam; (5) mangu (NOK pole) shaped beam; (6) sobhe (head ngadhu made of bamboo) shaped tube; (7) paja (roof truss of bamboo) formed triangle, rectangles, trapezoid. The geometry concept in the bhaga building are: (1) bhaga in the form of the beam; (2) roof (made of reeds) in the shape of a trapezoid and triangular prism; (3) pole shape of beams and tubes; (4) Ube (wall made of plank wood fai) shape of the rectangle; (5) Dawu (arranged boards) with carvings in the form of circles and triangle; (6) Soku bhotha and soku wi’i ( as a roof truss made of bamboo) shape tube rectangle, square and triangle. Geometry forms that exist in the ngadhu and bhaga in the Ubedolumolo Village are lines, angles, triangle, square, rectangle, trapezoid, circle, beam. Tube, cone and triangular prism.